Agama dan sains hubungan yang melengkapi - Augustine Harsono, Karima Audy (Maliki Interdisciplinary Journal, 2025)
This article discusses the complex relationship between religion and science, and how both can complement each other in understanding reality. Although often seen as conflicting, science and religion have a long history that demonstrates their potential for collaboration in providing a more holistic understanding of the world. In this context, the article explores the contributions of religion to the development of science, the challenges faced in integrating both in the modern era, and the opportunities for dialogue and collaboration. By emphasizing the importance of education that integrates religious values with scientific knowledge, this article suggests the need for interdisciplinary dialogue to build a deeper understanding of the roles of religion and science in human life. In conclusion, the synergy between religion and science can be key to addressing global challenges in the 21st century.